The Smartphone Annales: Japanese inventions and Western narratives throughout the history of mobile wireless telecommunication technology - Sneep, Deidre (Asia in Focus, 2018)
When it comes to the history of the smartphone, there is a general idea of the kind of technological achievements that led to its development. Most of these achievements are by US or European actors, while inventions that stem from other parts of the world, such as Japan for example, are largely excluded from the history of mobile phone technologies. As is usual with the construction of a canon of science and technology, the West constructs an image of itself as the classic ‘master of the machines’. Japan in this regard is an interesting case because over the years it has actually manifested an image of being technologically advanced, despite being a non-Western country. Nevertheless, its achievements in telecommunications have been largely overlooked. Written from a historiographic perspective, this paper discusses how inventions in mobile and wireless telecommunication technology that came from Japan have been either ignored or otherwise devalued, arguing that this is because of a dominant techno-orientalist narrative which has changed in form somewhat over time. Furthermore, the paper offers an explanation of how the canon of achievements of telecommunications came to be, thus contributing to the understanding of power dynamics in the global history of technology.